PEMBERDAYAAN UMKM DI ERA COVID-19 DALAM RANGKA PENGEMBANGAN DESA MANDIRI DAN SADAR PROKES 5M DI DESA PEMALI BANGKA - Karmawan Karmawan; M.Izhar Alamsyah; Syafri Yanto; Wulan Savitri (Universita Bangka Belitung, 2022)
This XVI KKN activity was carried out in the Air Pemali village, Pemali sub-district, Bangka Regency for 3 months, during the Covid 19 pandemic. This was achieved by several programs which were divided into 2, namely a planned work program and an unplanned work program. A planned work program is a work program which was previously designed and planned for a long period of time and an unplanned work program. Service activities during the Covid 19 pandemic in Pemali village by providing guidance to MSME actors in Pemali village. This activity provides education to perpetrators MSMEs during the Covid 19 pandemic. The next activity is to socialize the 5M program to schools in Pemali village so that awareness is formed to always carry out the 5M program which is in order to comply with government regulations and break the chain of COVID 19